The Effect of Multi-Asset Diversification on Resilience Indonesian Retail Investor Portfolio - Sari, Ni Kadek Wahyuni Merta; Yasa, I Putu Buda; Pranata, Andi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to analyze the effect of multi-asset diversification on the resilience of retail investor portfolios in Indonesia. Portfolio resilience is an important issue amidst global economic uncertainty, inflation and high capital market volatility. With increasingly open access to various investment instruments such as shares, bonds, gold, mutual funds and digital assets, retail investors now have the opportunity to reduce risk through portfolio diversification. This research uses a quantitative approach with simple linear regression analysis techniques. Data was collected from 100 active retail investor respondents who have investments in more than one asset class. The research results show that multi-asset diversification has a positive and significant influence on portfolio resilience. These findings reinforce the importance of asset allocation strategies in improving the financial stability of retail investors. The practical implication of these findings is the need for more intensive financial education to encourage optimal portfolio diversification practices among novice investors.